The sensitivity of pCO2 reconstructions in the Southern Ocean to sampling scales: a semi-idealized model sampling and reconstruction approach - Djeutchouang, Laique Merlin; Chang, Nicolette; Gregor, Luke; Vichi, Marcello; Monteiro, Pedro M. S. (Zenodo, 2021)
The data stored in this repository are part of the manuscript entitled "The sensitivity of pCO2 reconstructions in the Southern Ocean to sampling scales: a semi-idealized model sampling and reconstruction approach" submitted in consideration for publication for in European Geosciences Union: Biogeosciences. The netcdf file includes oceanographic (physical + biogeochemical) data, namely the partial pressure of carbon dioxide (pCO2) data at the surface ocean from the high-resolution (±10km) forced NEMO-PISCES coupled ocean model (BIOPERIANT12) and from the semi-idealized observing system simulation experiments (OSSEs) we performed.